Microfilaremic infection in canine filariosis in Colombia: a challenge in morphological and molecular diagnostics - Esteban-Mendoza, María Victoria; Arcila-Quiceno, Victor Hernán; Ríos Chacón, Catalina; Jaimes Dueñez, Jeiczon Elim; Tique Oviedo, Marisol; Díaz Bustos, Alejandro; Castellanos, María Fernanda; Morchón, Rodrigo (Frontiers in Veterinary Science, 2024)
Canine filariosis is a disease that can affect several species of animals, including humans, and is caused by filiform nematodes. They produce a wide range of symptoms that can often be confused with other diseases, which increases the complexity of diagnosis. The search for methodologies to facilitate diagnosis is a challenge, with specific and differential identification between parasite species being key. In Colombia, there is a problem of underdiagnosis in microfilaremic dogs infected by Dirofilaria immitis, microfilaremias not related to heartworm disease, and Acanthocheilonema reconditum. The highest prevalences have been reported for D. immitis although new cases of A. reconditum are beginning to appear. The aim of this study was to differentiate microfilariae infections by D. immitis and A. reconditum by morphological and molecular characterization of microfilariae to aid in the underdiagnosis of these canine filariosis in the metropolitan area of Bucaramanga (Colombia). For this purpose, 400 blood samples with anticoagulants were collected from dogs and analyzed with the commercial immunochromatography kit, for the detection of D. immitis circulating antigen, and with the Woo, Knott and PCR techniques for the count, morphological observation and molecular confirmation of microfilariae, respectively. The prevalence of microfilaremic dogs was 18.75% (75/400). The prevalence of dogs with positive antigen test and PCR for D. immitis was 1.25% (5/400) and 1% (4/400) respectively, 17.75% of microfilaremic dogs with positive PCR for A. reconditum (71/400) (first report in the metropolitan area of Bucaramanga) resulting in an animal co-infected by both species, and 0% for D. repens (0/400). However, by morphological characterization, 4% of the microfilariae (3/75) corresponded to D. immitis, 20% (15/75) to D. repens, and 76% (57/75) to A. reconditum. The use of molecular diagnostic methods such as PCR allows the specific identification of the parasite, being a more accurate method than the morphological identification of microfilariae, which helps to improve veterinary diagnosis in Colombia and will allow the establishment of an appropriate treatment for each species of filaria, providing reliable data to be used at clinical and epidemiological level.